Design, Fabrication and Control of Upper Limb Rehabilitation Robot Prototype for Stroke Patients - Shahrol, Mohamaddan; Annisa, Jamali; Ana Sakura, Zainal Abidin; Mohd Syahmi, Jamaludin; MUHAMAD FADZLI, ASHARI; Helmy, Hazmi (Journal of Advanced Manufacturing Technology (JAMT), UTEM, 2016)
Stroke is one of the prominent causes of disability in the world. In order to have chances for recovery, the stroke patients need repetitive and consistent rehabilitation activities or treatment. However, the increasing number of stroke patients with limited number of therapist and transportation problem for rural patients limits the possibility to have better treatment. This paper discussed the application of robotics system to support the rehabilitation activities focusing on the upper limb area of the body. The result shows two designs of upper limb rehabilitation device were fabricated and controlled. Both prototypes were emphasized on the compact, transportable/portable and simple operation concept. In order to evaluate the prototype, real patient test or experiment needs to be conducted.